Quality of care provided to patients with type 2 diabetes mellitus in Tshwane, South Africa - Ntlogeleng M. Mogale; Thembelihle S. Ntuli; Thembekile S. Dhlamini; Paul K. Chelule (AOSIS, 2024)
Background: Type 2 diabetes mellitus (T2D) is a public health challenge, affecting 90% of all patients with diabetes, globally. Compliance to treatment guidelines among healthcare professionals (HCPs) is low, thus resulting in inadequate quality of patient care and poor health outcomes among patients. Aim: To examine the availability of equipment, guidelines, screening and education offered to patients with T2D and compare between clinics and community health centres (CHCs). Setting: Tshwane Metropolitan Municipality, Gauteng Province, South Africa. Methods: A cross-sectional descriptive study utilised a self-administered questionnaire to collect data from nurses and doctors responsible for treating patients with T2D, from May to June 2022. About 250 eligible HCPs were recruited during routine morning meetings in 22 clinics and six CHCs. Results: More than 80% of HCPs reported having basic equipment except for ophthalmoscopes, Snellen charts (67%), tuning forks (64%), electrocardiograms (ECG) (46%) and monofilaments (12%). SEMDSA guidelines were reported by 16% of the participants, Diabetic Foot Care Guidelines were reported by 54% and Dietary Guidelines for Diabetic Patients by 55%. Furthermore, 91%, 71% and 69% of HCPs reported that ECG, microalbumin-creatinine and foot examinations were not always performed, respectively. About 66% and 17% always offered individual educational and group sessions, respectively. Conclusion: Equipment availability and compliance with treatment guidelines, patient education and screening of chronic complications are inadequate. Contribution: The study highlights the poor adherence to treatment guidelines and inadequate equipment in health facilities. These shortcomings could lead to missed opportunities for early diagnosis of complications and ultimately poorer patient outcomes.